A Shift from Efficiency to Adaptability: Recent Progress in Biomimetic Interactive Soft Robotics in Wet Environments. Issue 8 (24th January 2022) - Fang, Jielun; Zhuang, Yanfeng; Liu, Kailang; Chen, Zhuo; Liu, Zhou; Kong, Tiantian; Xu, Jianhong; Qi, Cheng
Abstract: Research field of soft robotics develops exponentially since it opens up many imaginations, such as human‐interactive robot, wearable robots, and transformable robots in unpredictable environments. Wet environments such as sea and in vivo represent dynamic and unstructured environments that adaptive soft robots can reach their potentials. Recent progresses in soft hybridized robotics performing tasks underwater herald a diversity of interactive soft robotics in wet environments. Here, the development of soft robots in wet environments is reviewed. The authors recapitulate biomimetic inspirations, recent advances in soft matter materials, representative fabrication techniques, system integration, and exemplary functions for underwater soft robots. The authors consider the key challenges the field faces in engineering material, software, and hardware that can bring highly intelligent soft robots into real world. Abstract : Recent progresses of soft robots performing tasks underwater herald a diversity of interactive soft robots in wet environments. Here, biomimetic inspirations, advances in soft matter materials, representative fabrication techniques, and exemplary functions are recapitualted for underwater soft robots. The authors consider key challenges in engineering material, software, and hardware that can highly intelligent soft robots into real world.